Maltoporin (LamB protein) contributes to the virulence and adhesion of Aeromonas veronii TH0426. Issue 3 (7th January 2019) - Yang, Bintong; Zhang, Dongxing; Wu, Tonglei; Zhang, Zhiqiang; Raza, Sayed Haidar Abbas; Schreurs, Nicola; Zhang, Lei; Yang, Guilian; Wang, Chunfeng; Qian, Aidong; Kang, Yuanhuan; Shan, Xiaofeng
Abstract: Aeromonas veronii is one of the main pathogens causing freshwater fish sepsis and ulcer syndrome. More and more cases have shown that it has become an important zoonotic and aquatic agent. In this study, a A. veronii TH0426 mutant strain (Δ lamB ) with an in‐frame deletion removed nucleotides 10–1, 296 of the lamB gene was firstly constructed to investigate its functions. The results showed that the LD50 value of the mutant Δ lamB to zebrafish and mice was 13.7‐fold and 5.6‐fold higher than those of the wild‐type strain, respectively. The toxicity of wild‐type strain to EPC cells was 2.1‐fold and threefold higher than those of ∆ lamB when infected for 1 and 2 hr. Furthermore, the ability of biofilm formation and the adhesion and invasion to EPC cells of ∆ lamB significantly decreased for 5.6‐fold and 1.8‐fold separately. In addition, motility detection result indicated that ∆ lamB lost the swimming ability. The results of flagellar staining and TEM demonstrated that the flagella of ∆ lamB were shed. In general, the deletion of lamB gene caused a significant decrease in the virulence and adhesion of A. veronii TH0426, and it can be known that the lamB gene of A. veronii plays a crucial role in the pathogenesis.